2019
DOI: 10.46963/mash.v2i1.26
|View full text |Cite
|
Sign up to set email alerts
|

“How Difficult English Is!” (An Attitude in Learning English for Non-English Students)

Abstract: English is one of the foreign languages taught from elementary to university. However, English is to be unswallowed bitter pill for non-English students. This is caused by the growing concepts of negative attitude about English, “English is frightening, English is hard to study, etc.” Attitude plays a vital role in learning any disciplines of knowledge includes English. Developing competencies and skills of English will not be achieved without noticing the supporting factors. In line with, this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…According to the document of students' English achievement, about 50% of students who got score below 75 as presented in graph 2 below. Numerous things might have an impact on them, such as attitudes, motivation, interest, learning style, and students' surroundings (Fadillah, 2014;Kurniawan & Sai'in, 2018;Anisa & Arifmiboy, 2021;Zulianti & Asari, 2022;Sanger, Rantung, & Corte_Real, 2022;Destomo, Istiatin, & Sudarwati, 2021;Pham & Huynh, 2018). Accordingly, the interview brought to light issues that students have when studying English, such as the ones listed below.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the document of students' English achievement, about 50% of students who got score below 75 as presented in graph 2 below. Numerous things might have an impact on them, such as attitudes, motivation, interest, learning style, and students' surroundings (Fadillah, 2014;Kurniawan & Sai'in, 2018;Anisa & Arifmiboy, 2021;Zulianti & Asari, 2022;Sanger, Rantung, & Corte_Real, 2022;Destomo, Istiatin, & Sudarwati, 2021;Pham & Huynh, 2018). Accordingly, the interview brought to light issues that students have when studying English, such as the ones listed below.…”
Section: Discussionmentioning
confidence: 99%
“…A learner with negative attitude may result in low learning achievement or achievement below their potential (Dachmiati, 2015). In the contrary, the learners with positive attitude and high self-esteem gives learners strong beliefs to get more opportunities to develop their potential to the fullest (Kurniawan & Sai'in, 2018;Sanger, Rantung, & Corte_Real, 2022). The interview revealed that confidence and self-esteem come to be issues the students should have in learning English.…”
Section: Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation